2020
DOI: 10.3390/ijms21020517
|View full text |Cite
|
Sign up to set email alerts
|

Substantiation for the Use of Curcumin during the Development of Neurodegeneration after Brain Ischemia

Abstract: Currently available pharmacological treatment of post-ischemia-reperfusion brain injury has limited effectiveness. This review provides an assessment of the current state of neurodegeneration treatment due to ischemia-reperfusion brain injury and focuses on the role of curcumin in the diet. The purpose of this review was to provide a comprehensive overview of what was published about the benefits of curcumin influence on post-ischemic brain damage. Some data on the clinical benefits of curcumin treatment of po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
47
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(50 citation statements)
references
References 158 publications
(324 reference statements)
1
47
0
Order By: Relevance
“…Curcumin is a major anti-inflammatory agent. Studies have shown inconsistent results regarding the effects of curcumin in different diseases [15][16][17][18][19]; but up to now, the anti-oxidant, anti-inflammatory and anti-angiogenic properties of curcumin have been reported in several animal and human studies [20][21][22]. Curcumin decreases the inflammation in diseases, including cancers.…”
mentioning
confidence: 99%
“…Curcumin is a major anti-inflammatory agent. Studies have shown inconsistent results regarding the effects of curcumin in different diseases [15][16][17][18][19]; but up to now, the anti-oxidant, anti-inflammatory and anti-angiogenic properties of curcumin have been reported in several animal and human studies [20][21][22]. Curcumin decreases the inflammation in diseases, including cancers.…”
mentioning
confidence: 99%
“…Further mechanistic studies have shown that the use of curcumin-Cu(II) or -Zn(II) complex systems inhibits cellular apoptosis by downregulating the nuclear factor κB pathway and increasing the regulation of the Bcl-2/Bax pathway [51]. To sum up, the presented study showed that the curcumin-Cu(II) or -Zn(II) complex systems show significant neuroprotective effects, suggesting the potential advantage of curcumin as a promising agent against Alzheimer's disease and post-ischemic neurodegeneration [52] and deserves further research.…”
Section: Intestinal Escherichia Fergusonii Escherichia Colimentioning
confidence: 67%
“…At present, in animal and clinical studies, toxicological evaluation has shown that curcumin is considered a pharmacologically safe substance at a dose of up to 12 g per day [52]. Currently, extrapolation of animal studies to clinical studies has shown that, in order to obtain beneficial effects in humans, it is recommended to take oral curcumin about 500 mg daily, which means that the daily intake of raw curcumin is about 4 g [52].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations